Pure and mixed ordered monolayers of tetracyano-2,6-naphthoquinodimethane and hexathiapentacene on the Ag(100) surface - Harbers, Robert (Beilstein J Nanotechnol, 2019)
We report on mixed ordered monolayers of the electron acceptor-type molecule tetracyano-2,6-naphthoquinodimethane (TNAP) and the electron donor-type molecule hexathiapentacene (HTPEN). This investigation was motivated by the general question which type of mixed stoichiometric structures are formed on a surface by molecules that are otherwise typically used for the synthesis of bulk charge-transfer materials. The layers were obtained by vacuum deposition on the Ag(100) surface and analyzed by low-energy electron diffraction (LEED) and scanning tunneling microscopy (STM). The formation of the mixed structure occurs spontaneously. An important motif for the structure formation is given by hydrogen bonds between the TNAP molecules. Both molecules, TNAP and HTPEN also form well-ordered monolayers on the Ag(100) surface on their own. In all structures, the molecules are adsorbed in a planar orientation on the surface. We discuss the influence of intermolecular charge transfer on the ordering in the mixed structure.